Traffic Calming Along Urban Roads Case Study: Central Business District, Johor Bahru - Wong, Kam Lee (2008)
Many rapidly developing cities are plagued with urban problems related to high level of motorization on the road. Contemporary measures adopted to address the issues of high motorization level are usually associated with engineering based capital improvement projects (CIPs). However, this will not necessarily overcome the traffic problems; in the long run, it will reproduce the same problem, at an even greater magnitude. CIPs also lead to the loss of urban heritage, natural elements and public amenities in the cities; and overall urban environmental degradation. It is time to look on to new measures to tackle the traffic problems. For this purpose, this research looks into the potentials of introducing traffic calming onto urban roads in the Central Business District (CBD) of Johor Bahru from traffic planning perspectives. Traffic calming aims at the total enhancement of road safety, improvement of traffic condition and betterment of the overall urban environment through vehicles speed reduction, deterring through traffic, encouraging pedestrianisation and cycling, and discouraging private vehicles usage. The research involves an inventory on site physical features; a road and intersection inventory; and weekdays and weekend observations on overall traffic condition. Site analysis shows that presently, the CBD of Johor Bahru faces serious traffic congestions especially during peak hours, due to high through traffic levels and limited east-west road linkages. There is a dire need for some measures to be implemented in order to reduce congestions and maintain the accessibility and attractiveness of the city, in line with the Johor Bahru District Local Plan 2020. This development plan had outlined in detail policies and guidelines for the development of the Johor Bahru Central District (including the CBD) augur well for the implementation of traffic calming in Johor Bahru. The development plan provides an opportunity to make a fresh start towards incorporating traffic calming into the new road network of the CBD.Questionnaire interviews with 90 business operators/ proprietors in the CBD of Johor Bahru shows a 44% agreement and 56% disagreement to the implementation of traffic calming in the CBD. The main reasons for disagreement include worries that business might deteriorate, current traffic volume is too high and lack of confidence in the effectiveness of traffic calming. Consultations with the city fire department and the hospital yield positive feedbacks whereas the police and the city bus operators consent to traffic calming on the condition that current traffic conditions be improved first. Evaluation on various traffic calming measures using the modified Goals Achievement Matrix (GAM) technique indicates that humped pedestrian crossings, raised plateau junctions, pavement widening, side road closures, bus priority lanes, speed cushions and flat top humps are suitable measures to be used on roads in the CBD. Finally, an area-wide scheme has been proposed within the CBD of Johor Bahru on collector roads, local roads and limited access controlled roads. Speed limits of 35 km/h to 50 km/h are proposed, to be achieved utilizing the 75-millimetre flat top humps, humped pedestrian crossing, raised plateau junctions, speed cushions, bus priority lanes, partial junction closure, gateway signage, rumble strips and 50-millimetre low height humps. It is concluded that traffic calming has the potential to be implemented on urban roads within the CBD and to be extended onto other urban roads.